INDUKSI AKAR TUNAS KE LAPA SAWIT (Elaeis guineensis Jacq.) SECARA IN VITRO DAN EX VITRO / Root Induction of Oil Palm (Elaeis guineensis Jacq.) Using In Vitro and Ex Vitro Techniques - Yunita, Rossa; MARISKA, IKA; PURNAMANINGSIH, RAGAPADMI; LESTARI, ENDANG GATI; UTAMI, SRI (Jurnal Penelitian Tanaman Industri, 2016)
Root induction is an important step in the process of propagation of plants through tissue culture techniques. For root induction commonly used plant growth regulator auxin, which has an important role in plant growth and development, especially at the stage of root initiation. The purpose of this study is to obtain appropriate methods for root induction of oil palm in vitro and ex vitro. The experiment used completely randomized factorial design, consisted of three main activities: (1) Induction of rooting on solid media, using combinations of NAA (2 and 4 mg/l) and IBA (1, 2, 3 and 4 mg/l) concentrations with 5 replications; (2) Induction of rooting the liquid media, using three concentrations of NAA (0, 3 and 6 mg/l), each treatment was replicated 5 times; (3) Induction of rooting ex vitro, using rootone F or IBA (20, 40 and 60 mg/l) with 5 replications. Results indicated that the best medium for in vitro root induction on solid media was MS + NAA 4 mg/l IBA + 4 mg/l, while for liquid media was MS + NAA 6 mg/l. Ex vitro rooting induction showed 60% success of acclimatization by soaking vitro shoots base in NAA solution 40 mg/l and 60 mg/l for 1 hour.Keywords: Elaeis guineensis Jacq., ex vitro, IBA, NAA